COVID‐19 outbreaks in aged‐care facilities in Australia. Issue 3 (5th December 2021) - Quigley, Ashley; Stone, Haley; Nguyen, Phi Yen; Chughtai, Abrar Ahmad; MacIntyre, C. Raina
Abstract: Background: Aged‐care facilities (ACF's) provide unique challenges when implementing infection control methods for respiratory outbreaks such as COVID‐19. Research on this highly vulnerable setting is lacking and there was no national reporting data of COVID‐19 cases in ACFs in Australia early in the pandemic. We aimed to estimate the burden of aged‐care worker (ACW) infections and outbreaks of COVID‐19 in Australian aged‐care. Methods: A line list of publicly available aged‐care related COVID‐19 reported cases from January 25 to June 10, 2020 was created and was enhanced by matching data extracted from media reports of aged‐care related COVID‐19 relevant outbreaks and reports. Rate ratios (RR) were used to predict risk of infection in ACW and aged‐care residents, and were calculated independently, by comparing overall cases to ACW and aged‐care residents' cases. Results: A total of 14 ACFs with COVID‐19 cases were recorded by June 2020 nationwide, with a high case fatality rate (CFR) of 50% ( n  = 34) and 100% ( n  = 3) seen in two ACFs. Analysis on the resident risk found that the COVID‐19 risk is 1.27 times higher (unadjusted RR 1.27 95% confidence interval [CI] 1.00 to1.61; P  = 0.047) as compared with the risk of infection in the general population. In over 60% of cases identified in ACFs, the source of infection in the index case was unknown. A total of 28 deaths associated within ACFs were reported, accounting for 54.9% of total deaths in New South Wales and 26.9% of total deaths in Australia. Conclusions: This high‐risk population requires additional prevention and control measures, such as routine testing of all staff and patients regardless of symptoms. Prompt isolation and quarantine as soon as a case is confirmed within a facility is essential.